Peculiar influence of linearly polarized spectrum illumination patterns onthe sensitivity characteristics of locust response to polarized light - Liu, Qihang; Zhao, Huiyuan; Zhang, Pingchuan; Cui, Jianxin; Gao, Guohong (International Journal of Agricultural and Biological Engineering, 2024)
This study investigated the influence of different linearly polarized spectrum lights on locusts polartactic responsecharacteristics linearly polarized vector sensitivity mode and polartactic response) by using linearly polarized spectrum vectorlight module and experimental device. The objective was to clarify the vector sensitivity characteristics and functional effect oflinearly polarized light spectrum intensity on locusts polartactic response, determine the influence specificity of linearlypolarized spectrum illumination properties on locusts polarization-related behavior. When spectrum and illumination wereconstant, locusts polartactic response, presenting the response feature of sine and cosine function change specificity, was relatedto spectrum attribute. The visual acuity effect stimulated by violet spectrum was the best, whereas the optical distancemodulation effect induced by orange spectrum was the strongest. When illumination was enhanced, locusts vector sensitivitymode shifted to present the specific sensitivity prompted by light intensity at long distance and inhibited by light intensity atshort distance. Moreover, the regulating function of violet spectrum was the strongest, and the regulatory mutation effect oforange spectrum was the least significant. Simultaneously, locusts polartactic sensitivity to 300° vector at 100 lx, whereas to240° vector at 1000 lx of linearly polarized violet light was the strongest. Locusts polartactic aggregation and visual tendencysensitivity to 90° vector at 100 lx, whereas to 270° vector at 1000 lx of linearly polarized violet light was the strongest. Theheterogeneous regulation function of different linearly polarized spectrum couplings with light intensity led to significantvariations in locusts vector sensitivity mode. This was derived from the antagonistic and specific tuning characteristics oflocusts polartactic vision, reflecting the integrated output effect of locusts vector dependence regulated by linearly polarizedspectrum intensity attribute. The findings were significant for the construction of pest polarization induction light sources andthe investigation of the sensitive physiology pathway of locusts polarization vision.Keywords: Locusta migratoria, linearly polarized light, spectrum illumination pattern, locusts polar axis response, vectorDOI: 10.25165/j.ijabe.20241702.8235Citation: Liu Q H, Zhao H Y, Zhang P C, Cui J X, Gao G H. Peculiar influence of linearly polarized spectrum illuminationpatterns on the sensitivity characteristics of locust response to polarized light. Int J Agric & Biol Eng, 2024; 17(2): 59–67.